AN ANALYSIS OF STUDENTS’ INTEREST OF READING ENGLISH NOVEL IN FACULTY OF LETTERS MUSLIM NUSANTARA AL-WASHLIYAH UNIVERSITY - Rezky Khoirina Tarihoran; Ratna Sari Dewi (IKIP Siliwangi, 2020)
This research was aimed to find out how the condition of students’ interest in reading English novels in Faculty of Letters, Muslim Nusantara University Al-Washliyah. As a student majoring in English Literature, reading novels is one of the activities that must be carried out because most of the subjects given are closely related to centrality, one of which is an English-language novel. This research was conducted at the fifth semester students of the Faculty of Literature at Muslim Nusantara University Al-Washliyah. This research used a qualitative descriptive method. The instruments used were observation and interviews. Based on the results of the study it was found that the condition of students’ interest of reading English novels in Faculty of Letters, Muslim Nusantara Al-Washliyah University is very poor. Keywords: Analysis, Reading, Novel